Influence of the story stiffness of reinforced concrete frame with proportional hysteretic dampers on the seismic response (2011)
This paper investigates the influence of the story stiffness of reinforced concrete (R/C) frame on the seismic response of R/C buildings with proportional hysteretic dampers. For this purpose, non-linear time-history analyses were conducted on a series of multi-degree-of-freedom system models that include a wide range of structural parameters and vertical distributions of story stiffnesses and strengths of R/C main frame and dampers. Although the basic purpose of damper installation is to reduce deformation demands, the results of analyses indicate that the story-drift demand on an entire system could be larger than that of the structure without dampers, depending highly on the stiffness and response period of R/C main frame. Moreover, dampers are shown to be more efficient in reducing the story-drift demand when installed into a flexible R/C main frame.